34th AIAA Applied Aerodynamics Conference 2016
DOI: 10.2514/6.2016-3554
|View full text |Cite
|
Sign up to set email alerts
|

Lift and Drag of Flapping Membrane Wings at High Angles of Attack

Abstract: An experimental study was undertaken to assess the aerodynamic benefits of flapping in forward flight at various Reynolds numbers and flapping frequencies. The test article is a commercially available ornithopter whose flapping wing is a flexible membrane. Analysis has focused on the time-averaged aerodynamic performance (i.e. mean lift and thrust/drag). Results to date reveal a consistent trend in the variation of the thrust produced with changes in flapping frequency and angle of attack. These results are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Open Sci. 8: 210452 different flapping wing vehicle configurations, including design tools for concepts developed for forward [42,43] and hovering [44] flight modes. Recent progress in miniaturization of engineering systems together with the desire to create tiny aerial robots have motivated the development of a range of flapping wing vehicle concepts at insect-scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open Sci. 8: 210452 different flapping wing vehicle configurations, including design tools for concepts developed for forward [42,43] and hovering [44] flight modes. Recent progress in miniaturization of engineering systems together with the desire to create tiny aerial robots have motivated the development of a range of flapping wing vehicle concepts at insect-scale.…”
Section: Discussionmentioning
confidence: 99%
“…The development of flapping wing vehicles requires generic toolsets that would allow conceptual design/sizing of such vehicles while taking into consideration the correct interaction between the different subsystems in a transparent fashion. Design methods have been previously presented for different flapping wing vehicle configurations, including design tools for concepts developed for forward [ 42 , 43 ] and hovering [ 44 ] flight modes. Recent progress in miniaturization of engineering systems together with the desire to create tiny aerial robots have motivated the development of a range of flapping wing vehicle concepts at insect-scale.…”
Section: Discussionmentioning
confidence: 99%
“…. (5) Instantaneous variations of the differences in the force coefficients for all the five wing planforms are shown in Fig. 9(a) and (b).…”
Section: Variation In Instantaneous Force Coefficients Over a Gust Cyclementioning
confidence: 99%
“…Fluid dynamics of flapping wings in various modes of flight viz. hover (4) and forward flight (5) have been studied. Apart from assessing the flow physics of single wing, studies have also been reported on tandem wings with different inter-wing positions (6) and relative kinematics (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Zakaria et al (2015) showed that the inclusion of intertial power requirements is essential for physical and proper optimization [6]. They further studied the aerodynamic forces generated in forward flight for different Reynolds numbers and flapping frequency [7]. Whitney (2012) designed and developed one of the tiniest FWMAVs [8].…”
Section: Introductionmentioning
confidence: 99%